Scalp seborrheic dermatitis demonstrates a skewing of Th1 activation: a proteomic study in lesional skin - Shen, Ningning; Chen, Wei; Hu, Lihua; Huang, Jia; Dong, Qiang (Frontiers in Immunology, 2025)
IntroductionScalp seborrheic dermatitis (SSD) is a common, chronic inflammatory skin disease. Its pathogenesis and immunological features have been poorly studied.ObjectiveTo elucidate the molecular profile of adult patients with SSD in lesional scalps.MethodsUsing punch biopsies, we assessed 92 inflammatory biomarkers in the lesional scalps of SSD patients (n=16) and demographically matched healthy controls (HCs; n=12) via Olink high-throughput proteomics.ResultsWe identified 16 differentially expressed proteins (DEPs) between lesional scalps of patients with SSD and those of HCs. SSD lesional scalps demonstrated significantly greater expressions of proteins related to T-cell/lymphocyte activation, the cytokine storm signaling pathway and the CGAS-STING signaling pathway. Ingenuity pathway analysis (IPA) highlighted Th1 skewing. These data suggest that SSD is associated with Th1 skewing and the dysregulation of lipid metabolism.ConclusionThese analyses provide a rationale for novel treatment approaches for SSD patients, mainly those targeting Th1 pathways.